2014
DOI: 10.18052/www.scipress.com/ilcpa.25.61
|View full text |Cite
|
Sign up to set email alerts
|

Easy, Simplistic and Green Synthesis of Various Benzimidazole and Benzoxazole Derivatives Using PEG<sub>400</sub> as a Green Solvent

Abstract: An improved environmentally benign procedure for the synthesis of various benzimidazole and benzoxazole derivatives using green solvent PEG400. We have optimized the reaction condition and it was found that PEG400 was believed to be best as compared to PEG200, PEG600 and PEG800 at 80 to 85 °C. This method provides a novel route for the synthesis of benzimidazole and benzoxazole derivatives. The main attractive features of this process are a mild reaction conditions, easy workup procedure and good to excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Green chemistry (GC) involves the use of a set of principles that reduces or removes the use or formation of hazardous substances in the design, manufacture, and application of chemical products [46]. As we design new chemical synthesis, decisions about what hazardous substances are used and what toxic materials should be handled are being made.…”
Section: Discussionmentioning
confidence: 99%
“…Green chemistry (GC) involves the use of a set of principles that reduces or removes the use or formation of hazardous substances in the design, manufacture, and application of chemical products [46]. As we design new chemical synthesis, decisions about what hazardous substances are used and what toxic materials should be handled are being made.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction system gives the best yield in PEG‐400 at 80–85 °C. This reaction route is the novel route using PEG and reaction under Glycerol/water method are reported for the synthesized target molecule (Scheme ) …”
Section: Classificationmentioning
confidence: 99%
“…This reaction route is the novel route using PEG and reaction under Glycerol/water method are reported for the synthesized target molecule (Scheme 38). [84] Kathirvelan et al in 2013 reported one-pot good yield synthesis scheme of MSB (143 a-c) scaffold by the condensation of benzene-1,2-diamine (141) with various aldehyde (142) in the presence of green and economically viable catalyst ammonium chloride at 80-90 °C give moderate to better yield (143 a-c)(Scheme 39). [85] Peng et al reported a method in 2012 for the synthesis of benzimidazole (144 a-b) ring system via intermolecular cyclization of N-(2-iodoaryl) benzamidine (144) in presence of base, at 100 °C potassium carbonate and caesium carbonate used as a base to gives the best yield of product (144 a-b).…”
Section: Photo-catalysed Reactionmentioning
confidence: 99%
See 1 more Smart Citation